PHYTOCHEMICAL SCREENING, FREE RADICAL SCAVENGING AND ANTI-INFLAMMATORY ACTIVITY OF CROTON LEPTOSTACHYUS KUNTH LEAF EXTRACTS. - SÁNCHEZ PERALTA, WILMER FERNANDO; OSPINA GIRALDO, LUIS FERNANDO; PÉREZ JARAMILLO, CLAUDIA CRISTINA; ARANGO, WALTER MURILLO; MÉNDEZ ARTEAGA, JOHN JAIRO (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To study the biological potential of Croton leptostachyus Kunth (Mosquero) leaves through phytochemical screening and determination of the free radical scavenging capacity (against DPPH. and ABTS.+) and anti-inflammatory activity via a TPA induced auricular edema model in ICR mice of the crude ethanolic extract and subextracts (of n-hexane, ethyl acetate and ethanol). Materials and methods: The C. lepstostachyus leaf extracts were obtained via ethanolic maceration and subsequent partition of the dry ethanolic crude extract with n-hexane and ethyl acetate, the aforementioned samples were tested for phytochemical composition, antiradical activity (DPPH. and ABTS.+), and anti-inflammatory activity (TPA induced auricular edema model in mice). Results: The phytochemical plant profile showed a diversity of secondary metabolites such as terpenic compounds (triterpenes and saponins), phenolics (flavonoids, tannins and phenylpropanoids), alkaloids and a minor proportion of iridoids and coumarins. Free radical scavenging assays indicated a presumable combined effect of the C. leptostachyus leaf metabolites considering the fact that the crude extract was the most active scavenger of DPPH. and ABTS.+. However, between the subextracts, the ethanolic subextract showed the highest antiradical activity, indicating a presumable major contribution of phenolic compounds in this result. The topical anti-inflammatory action of ethyl acetate subextract showed a possible enhanced effect due to a higher concentration of medium polarity compounds; no anti-inflammatory activity of the subsequent fractions of this sample was observed, indicating a probably interaction of the metabolites contained therein. Conclusion: C. leptostachyus leaf extracts showed potential as free radical scavengers and anti-inflammatory compounds sources. Keywords: Croton leptostachyus, Free radical scavenging activity, Anti-inflammatory activity.